The Impact of Social Media on the Interaction Between Students and Teachers at the University of Halabja - Atta Abdalwahid Ahmed; Marwan Mazhar Jafr; Mariwan Ahmed Hama Saeed; Aram Omer Ali; Bahaaldeen Faraj Mahmood; Shahrazad Naib Muhammad; Shamal Azad Abdullah (Engiscience Publisher, 2022)
The aim of this article is to investigate the role of web 2.0 tools and social media applications in the relationship between undergraduate students and university lecturers. The researchers used the quantitative approach to design the methodology of the research. The sample of the study was 85 students from the departments of (Social Sciences, Arabic Language, and English Language) in the second year, third year, and fourth year at the college of basic education at the University of Halabja for the academic year 2020-2021. The questionnaire was used to collect the data from the participants. The result of the study demonstrated that there was a significant influence on the relationship between the students and the lecturers in using social media applications. Students showed that they use social media every day and it has a positive impact on their interaction with the lecturers.